Integrating invasive species policies across ornamental horticulture supply chains to prevent plant invasions. Issue 1 (18th July 2017) - Hulme, Philip E.; Brundu, Giuseppe; Carboni, Marta; Dehnen‐Schmutz, Katharina; Dullinger, Stefan; Early, Regan; Essl, Franz; González‐Moreno, Pablo; Groom, Quentin J.; Kueffer, Christoph; Kühn, Ingolf; Maurel, Noëlie; et al.
Abstract: Ornamental horticulture is the primary pathway for invasive alien plant introductions. We critically appraise published evidence on the effectiveness of four policy instruments that tackle invasions along the horticulture supply chain: pre‐border import restrictions, post‐border bans, industry codes of conduct and consumer education. Effective pre‐border interventions rely on rigorous risk assessment and high industry compliance. Post‐border sales bans become progressively less effective when alien species become widespread in a region. A lack of independent performance evaluation and of public disclosure, limits the uptake and effectiveness of voluntary codes of conduct and discourages shifts in consumer preference away from invasive alien species. Policy implications . Closing the plant invasion pathway associated with ornamental horticulture requires government‐industry agreements to fund effective pre‐ and post‐border weed risk assessments that can be subsequently supported by widely adopted, as well as verifiable, industry codes of conduct. This will ensure producers and consumers make informed choices in the face of better targeted public education addressing plant invasions.